Attentional and emotional brain response to message framing in context of green marketing. Issue 9 (September 2020) - Zubair, Muhammad; Wang, Xiaoyi; Iqbal, Sidra; Awais, Muhammad; Wang, Ruining
Abstract: Background: Message framing plays an important role in advertising strategies and has been studied from various perspectives in different behavioral studies. New method: This study employs the event-related potential technique to examine attentional and emotional brain processing as influenced by message framing in the context of green marketing. Results: The behavioral results demonstrated that purchase preference was higher under positive framing compared to negative and neutral framing. As per the event-related potential results, negative framing elicited a larger P1 component, which reveals that in the first stage of processing information, threatening information attracted more attention. In the second and third stage, N170 and P3, respectively, were higher for positive framing, demonstrating that there was more attention toward the processing of non-threatening emotional information. Comparison with existing method: Message Framing has been previously examined with behavioral methods. We for the first time examined it with a neuroscientific method like Event Related Brain Potential technique in a green marketing context. Conclusion: Our results compared to behavioral studies provide stronger evidence from underlying neural perspective for how message framing can be affected by attentional and emotional brain responses in the context of green marketing. Abstract : Attention; Emotion; Event-related brain potentials; Green marketing; Message framing; ERPs; Consumer attitude; Research and development; Consumer psychology; Decision analysis; Cognition